Prinsip Kesantunan Berbahasa dalam Kolom Komentar Kanal Youtube Metrotvnews dan Implikasinya terhadap Pembelajaran Teks Persuasi - Novira Amir; Tressyalina Tressyalina (Universitas Negeri Padang, 2023)
The purpose of this research is. First, describe compliance with the politeness principle in the comment column on the metrotvnews YouTube channel. Second, describe violation of the principle of politeness in language in the comment column on the metrotvnews YouTube channel. Third, describing the language context in the comment column on the metrotvnews YouTube channel. This research used qualitative with a descriptive method. The data are speech that contain compliance to politeness principles, violations of politeness principles from the comment column on the metrotvnews YouTube channel. The research instrument is the researcher himself. The data collection techniques used in this study were the simak bebas libat cakap technique, the documentation technique and the note-taking technique. Data analysis techniques are carried out by organizing data, describing it into units, synthesizing, compiling into patterns, and making conclusions. The research results show three things. First, found 59 data on compliance with the politeness principle consisting of 2 compliance with tact maxim, 25 compliance with approbation maxim, 9 compliance with agreement maxim and 23 compliance with sympath maxim. Second, there were 41 violations of the politeness principle consisting of 12 violations with tact maxim, 1 violation with generousity maxim, 24 violations with approbation maxim, 2 violations with agreement maxim and 2 violations with sympath maxim. Third, the language context is polite, and impolite. It can be concluded that. First, the most dominant form of compliance politeness principle is approbation maxim. Second, the most dominant form of violation politeness is a approbation maxim. Third, the most dominant language context in the comment column on the metrotvnews YouTube channel is polite. This research can be implicated in persuasion text learning.